Elucidation of the identification mechanism of murine embryonic cryotolerance through metabolomic analyses and the study of cellular ultrastructures / Nor Ashikin Mohamed Noor Khan - Noor Khan, Nor Ashikin Mohamed; Rajikin, Mohd. Hamim; Froemming, Gabriele Ruth Anisah; Abdul Satar, Nuraliza; Ibrahim, Mohd Johari; Dasiman, Razif (Research Management Institute (RMI), 2012)
Cryopreservation of embryos is an essential procedure in all assisted conception units. Prediction of embryonic cryotolerance and developmental capacity after cryopreservation has previously relied on morphological assessment and observation on developmental capacity (Kuleshova et al., 2001; Han et al., 2003). Technological advancements in recent years has allowed for high-resolution microscopy in which details of ultrastructure at the organelle level may be used to select viable embryos for transfer (Dailey et al., 2006; Yamagata et al., 2009). In these studies, disruption to cytoskeletal components and mitochondrial distribution are observed and used in the selection of viable embryos. Although selection done based on qualitative morphological criteria produces valuable information on the physical damages after cryopreservation, the use of quantitative methods has proven to be more accurate in predicting survivability (Stokes, et al., 2007). Metabolomics is a useful quantitative tool to predict viability of embryos for transfer (Katz-Jaffe et al., 2009). With regard to metabolomics, amino acid turnover in the culture media (Houghton et al. 2002: Brison et al. 2007) and measurements of key functional groups using near-infrared spectroscopy (NIR) (Vergouw et al. 2009) has been used effectively to predict embryo developmental capacity.